Organic carbon biodegradability and heterotrophic bacteria along a combined sewer catchment during rain events - Seidl, M.; Servais, P.; Martaud, M.; Gandouin, C.; Mouchel, J.M. (Water Science and Technology, 1998)
The aim of this study was the evaluation of fluxes of organic carbon and biodegradability of waste waters during rain events in order to better predict the impacts of combined sewer overflows (CSO). The combined sewer system studied was located in a densely populated urban catchment adjacent to Paris. Five subcatchments of different size, have been monitored during several rain events for suspended solids, conductivity, ammonium, chemical and biological oxygen demand. In addition, two of these subcathments have been evaluated for dissolved and particulate organic carbon, their biodegradable fractions, and the total bacterial biomass. Several indexes, indicate a lower degradability of waste water during dry weather at the downstream stations, accompanied by an increase of bacterial size and bacterial biomass. A further decrease of biodegradable organic carbon related to rain intensity can be seen at all stations. Our results show a higher proportion of refractory organic carbon during rain events than during dry weather with a possible contribution of the in-sewer sediments to the bacterial wet weather flux. (C) 1998 IAWQ. Published by Elsevier Science Ltd.